Changing the assortment of available food and drink for leaner, greener diets. (13th April 2022) - Marteau, Theresa M; Hollands, Gareth J; Pechey, Rachel; Reynolds, James P; Jebb, Susan A
Abstract : Theresa Marteau and colleagues discuss the potential of "availability interventions" to improve diets and reduce inequalities